2022
DOI: 10.1002/path.5905
|View full text |Cite
|
Sign up to set email alerts
|

Integrating computational pathology and proteomics to address tumor heterogeneity

Abstract: Despite numerous advances in our molecular understanding of cancer biology, success in precision medicine trials has remained elusive for many malignancies. Emerging evidence now supports that these challenges are partly driven by proteogenomic discordances across molecular readouts and heterogeneous biology that is spatially distributed across tumors. Here we discuss these key limitations and how integrating the promise of mass-spectrometry-based global proteomics and computational imaging can help prioritize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…Intra-tumoral heterogeneity has emerged as a key concept in current precision medicine efforts 42 . While there have been technological breakthroughs to map such spatial biodiversity at the genomic, transcriptomic and proteomic level, the relative discord between the upper limits of tissue profiling throughput and tumor sizes creates an important bottleneck for comprehensive analysis of most tumor specimens 2,4,7 . Here, we highlight how a neural network-based tool (HAVOC) can detect and quantify spatial distributions of cancer biodiversity across not only individual sections, but also on larger (entire) tumor specimens in a hypothesis-agnostic manner.…”
Section: Discussionmentioning
confidence: 99%
“…Intra-tumoral heterogeneity has emerged as a key concept in current precision medicine efforts 42 . While there have been technological breakthroughs to map such spatial biodiversity at the genomic, transcriptomic and proteomic level, the relative discord between the upper limits of tissue profiling throughput and tumor sizes creates an important bottleneck for comprehensive analysis of most tumor specimens 2,4,7 . Here, we highlight how a neural network-based tool (HAVOC) can detect and quantify spatial distributions of cancer biodiversity across not only individual sections, but also on larger (entire) tumor specimens in a hypothesis-agnostic manner.…”
Section: Discussionmentioning
confidence: 99%
“…While this has significantly furthered our biological models of the brain and various neuropathologies, including neurodegeneration [39,40] and malignancies [41] recent proteogenomic comparisons have shown that downstream phenotypic programs cannot always be reliably inferred from transcriptional readouts (R = ∼0.35) [42][43][44]. Therefore, there is a need to complement these genomic atlases with spatially preserved proteomic profiles in tissue and cell-types specific profiling of complex experimental modes [45].…”
Section: Challenges With Proteomic Characterization Of Human Neural T...mentioning
confidence: 99%
“…Some emerging protocols even allow for single-cell analysis of hundreds of proteins per cell [46][47][48]. While there are, of course, important advantages and limitation to each of these strategies, the spatial organization of many important aspects of tissue and disease heterogeneity offer an opportunity to profile relatively biologically enriched tissue compartments to achieve higher and potentially more meaningful profiling depths [45]. Over the years, our group has significantly invested in this neuroanatomical strategy to decipher the dynamic proteome of the brain and disease, including different stages and regions of the developing brain, common tumor malignancies, and cell-type-specific enrichment and profiling of cerebral organoid tissue.…”
Section: The Brain Protein Atlas: a Proteomic Catalog Of Spatially An...mentioning
confidence: 99%
See 1 more Smart Citation
“…The final review in this section is from Dent and Diamandis (Toronto, Canada) and deals with the use of computational pathology to address the issue of intra‐tumoural heterogeneity, in this case applied to guide objective proteomic analysis and support the design of personalised combination therapeutic combinations [6]. This notion of combining ‘omics technologies with spatial information from image analysis is an exciting area for the future.…”
Section: Digital Pathologymentioning
confidence: 99%